Preparedness to Identify and Care for Trafficked Persons in South Carolina Hospitals: A State-Wide Exploration. Issue 3 (26th May 2020) - Armstrong, Stephanie; Greenbaum, V. Jordan; López, Cristina; Barroso, Julie
ABSTRACT: This qualitative descriptive study utilized stratified purposive sampling to investigate how prepared hospitals throughout the state of South Carolina were to identify and care for individuals experiencing human trafficking. Hospitals were invited to participate if trafficking had been reported to the National Human Trafficking Hotline, in 2016, in their geographic location. Telephone interviews were conducted with Emergency Department (ED) directors/managers due to their knowledge of clinical practices and policies/procedures within the ED, as well as evidence that trafficking victims frequently seek care in this setting. Eighteen hospitals comprised the final sample with facilities from all four regions of the state represented. Statewide, hospitals were lacking human trafficking response protocols, healthcare professionals had not received training about human trafficking, and safety issues surrounding care of this population were frequently unrecognized. The majority of healthcare professionals (HCPs) believed trafficking occurred in their area; yet, few believed they had cared for a victim. South Carolina hospitals have many opportunities to improve their responses to trafficked persons, including developing and implementing human trafficking response policies/protocols; providing training for HCPs; ensuring the safety of victims, HCPs and others; fostering relationships with local service providers; and increasing community engagement and education on this topic.